(untitled) (JURNAL KEPERAWATAN, 2018)
Abstarct : Nutritional status is the measure of succes in fulfillment of nutrition for children indicated by weight and height. Breakfast is the energy supply to the brain is best so that you can concentrate in school. This Purpose aims to know the relationship of nutritional status and quality of breakfast with the achievement studied at SD Negeri 21 Manado. Design Research with Cross Sectional. Sampling in this research are the Total Sampling there are 51 respondents research. The Result of the Research using instruments qustionnaries, observation sheets, the value of report cards and statistical test Chi-Square at the level if significance of 95% (Î±=0.05). the result showed there are 23 respondents were ini the category of less nutrtional status and 23 respondents are on the requirements of quality breakfast and 25 respondents were in category a grade of C or less. The Chi-Square test result indicate that there is a relatioship of nutritional status with the achievement studied at SD Negeri 21 Manado where p= 0.004 value smaller than Î±=0.05 and there is a connection with the breakfast quality achievement studied at SD Negeri 21 Manado where the value of p= 0.000 is smaller tahn Î±=0.05. Conclusion the results of this study showed no relathioship between nutritional status and quality of breakfast with the learning achievments of students of class IV dan V SD Negeri 21 Manado. Key words : Nutritional Status, The Quality Of Learning Achievements, Full Breakfast. Abstrak : Status gizi adalah ukuran keberhasilan dalam pemenuhan nutrisi untuk anak yang diindikasikan oleh berat badan dan tinggi badan. Sarapan pagi merupakan pasokan energi untuk otak yang paling baik agar dapat berkonsentrasi di sekolah. Tujuan Penelitian ini untuk mengetahui hubungan status gizi dan kualitas sarapan pagi dengan prestasi belajar siswa di SD Negeri 21 Manado. Desain Penelitian ini dengan pendekatan Cross Sectional. Sampel dalam penelitian ini adalah Total Sampling terdapat 51 reponden. Penelitian ini menggunakan instrumen kuesioner, lembar observasi , nilai raport dan uji statistik Chi-Square pada tingkat kemaknaan 95% (Î±=0.05). Hasil Penelitian terdapat 23 responden berada pada ketegori status gizi kurang dan 23 responden berada pada ketegori kualitas sarapan pagi yang cukup dan 25 responden berada pada kategori Nilai C/kurang dengan menggunakan uji Chi-Square menunjukan ada hubungan status gizi dengan prestasi belajar di SD 21 Manado dimana nilai signifikan 0.004 lebih kecil dari Î±=0.05 dan ada hubungan kualitas sarapan pagi dengan prestasi belajar di SD Negeri 21 Manado dimana nilai signifikan 0.000 lebih kecil dari Î±=0.05. Simpulan hasil peneltian ini menunjukan ada hubungan antara status gizi dan kualitas sarapan pagi dengan prestasi belajar pada siswa kelas IV dan V di SD Negeri 21 Manado. Kata kunci : Status Gizi, Kualitas Sarapan Pagi, Prestasi Belajar